EROSION CHARACTERISTICS OF SELECTED SOUTHWESTERN NIGERIAN SOILS IN RELATION TO SOIL PHYSICOCHEMICAL PROPERTIES, OVERLAND FLOW AND CHEMICAL CONDITIONING - OYEDELE , D. J.; AINA, P. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Erosion was evaluated by the laboratory rainfall simulator for 5 widely distributed agricultural soils from Nigeria in relation to soil physicochemical properties and effects of overland now (at equivalent 33 and cm/hr) and chemical conditioning with ethylene glycol. Rainfall intensities Of 12.5. 15.7. tad 24.1 cm/hr were used on soil micro-plots tilted at 5% and 9% slopes. Erodibility of the soils varied with indices ranging from 0.017 to O. 157, and was related to soil contents of organic matter, sequioxides and 2.250.urn diameter particle fraction. Overland flow constituted a significant causative factor, causing as much as 33% erosion compared to rainfall erosion on some soils. The results ascertained the seveity Of erosion in the study area and also the possible use of ethylene glyco: in erosion control without adverse effects on maize crop establishment.